Electron density measurement in atmospheric pressure plasma jets: Stark broadening of hydrogenated and non-hydrogenated lines. (16th April 2015) - Nikiforov, A Yu; Leys, Ch; Gonzalez, M A; Walsh, J L
Abstract: Electron density is one of the key parameters in the physics of a gas discharge. In this contribution the application of the Stark broadening method to determine the electron density in low temperature atmospheric pressure plasma jets is discussed. An overview of the available theoretical Stark broadening calculations of hydrogenated and non-hydrogenated atomic lines is presented. The difficulty in the evaluation of the fine structure splitting of lines, which is important at low electron density, is analysed and recommendations on the applicability of the method for low ionization degree plasmas are given. Different emission line broadening mechanisms under atmospheric pressure conditions are discussed and an experimental line profile fitting procedure for the determination of the Stark broadening contribution is suggested. Available experimental data is carefully analysed for the Stark broadening of lines in plasma jets excited over a wide range of frequencies from dc to MW and pulsed mode. Finally, recommendations are given concerning the application of the Stark broadening technique for the estimation of the electron density under typical conditions of plasma jets.